2017
DOI: 10.1007/s00276-016-1802-y
|View full text |Cite
|
Sign up to set email alerts
|

Perforator variability in the anterolateral thigh free flap: a systematic review

Abstract: The ALT free flap is a reconstruction option in head and neck cancer. Adequate perforators for reconstruction are identified in the majority of cases. Increased anatomical perforator knowledge may lead to further uptake of ALT free flap reconstruction and improved intraoperative troubleshooting. Further studies investigating those patients with no perforators in the ALT may lead to improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…According to some studies, the ALT flap could be considered as the first choice for reconstructing wounds of children except for those with bone defects. The advantages of ALT flaps in adult have been summarized in the literature (21)(22)(23)(24). During the operation, we found the absolute size of the pedicle vessels of children to be smaller than that of adults, but their relative size in relation to the patient body was greater than that in adults, which is consistent with a previous report by Van Landuyt et al (5).…”
Section: Discussionsupporting
confidence: 90%
“…According to some studies, the ALT flap could be considered as the first choice for reconstructing wounds of children except for those with bone defects. The advantages of ALT flaps in adult have been summarized in the literature (21)(22)(23)(24). During the operation, we found the absolute size of the pedicle vessels of children to be smaller than that of adults, but their relative size in relation to the patient body was greater than that in adults, which is consistent with a previous report by Van Landuyt et al (5).…”
Section: Discussionsupporting
confidence: 90%
“…Multiple branches enter the flaps as the perforating branches to nourish the flaps 13 . In a systematic review with analysis on 1251 thighs described in 23 articles, Smith et al 27 . revealed that the average number of perforating branches is 1.15–4.26.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple branches enter the flaps as the perforating branches to nourish the flaps 13 . In a systematic review with analysis on 1251 thighs described in 23 articles, Smith et al 27 revealed that the average number of perforating branches is 1.15-4.26. The lateral femoral muscle belongs to a single main artery muscle, and the muscular branches are constantly present in a multi-branch pattern.…”
Section: The Characteristic Of Chimeric Anterolateral Thigh Perforator Flapmentioning
confidence: 99%
“…Some reports have described the absence of cutaneous perforators arising from the descending branch of the lateral circumflex femoral artery in a small proportion of cases involving the ALT flap. 15 Identification of an available perforator might be facilitated by much more carefully searching for and dissecting the perforator as well as meticulously dissecting and separating the semitranslucent connective membrane encapsulating the stem vessel bundle. Although anatomical variations were encountered in the present study, planning the ALT flap based on established anatomical markers was still valid.…”
Section: Discussionmentioning
confidence: 99%